Different Stabilization Techniques for Type 62B3 Acetabular Fractures in Combination With Primary Total Hip Arthroplasty in Elderly Patients: A Biomechanical Comparison - Uvarovas, Valentinas (Geriatr Orthop Surg Rehabil, 2016)
INTRODUCTION: The total hip arthroplasty (THA) as part of acute fracture management is used for acetabular fractures in elderly patients. Our objective was to assess the stability of osteosynthesis performed using 2 different techniques in combination with THA in an experimental model. MATERIALS AND METHODS: We conducted 20 experiments using the left-side hemipelves composite bone models. There were 2 testing groups: 1- and 2-stage osteosynthesis. The acetabular fractures of the anterior column and posterior hemitransverse were simulated. The same THA technique was used in both groups. The stability of osteosynthesis was explored and compared between the groups by measuring the fracture displacement of anterior and posterior columns under the standardized test load (1187 N) protocol. Load distance diagrams were generated. RESULTS: The 0.680-mm gap (0.518; 1.548) of the posterior column in the 1-stage group (n = 10) was higher than the 0.370-mm gap (0.255; 0.428) in the 2-stage group (n = 10; P = .002). There was no significant difference between the gap of the anterior column in the 1- and 2-stage groups (0.135 [0.078; 0.290] mm vs 0.160 [0.120; 0.210] mm; P = .579). CONCLUSION: The 2-stage osteosynthesis of the anterior and posterior columns in combination with THA provides better stability of posterior column when compared to 1-stage method in composite bone models.